Methodological Rigor and Temporal Trends of Cardiovascular Medicine Meta‐Analyses in Highest‐Impact Journals - Dhruv Mahtta (Wiley, 2021)
Background Well‐conducted meta‐analyses are considered to be at the top of the evidence‐based hierarchy pyramid, with an expansion of these publications within the cardiovascular research arena. There are limited data evaluating the trends and quality of such publications. The objective of this study was to evaluate the methodological rigor and temporal trends of cardiovascular medicine‐related meta‐analyses published in the highest impact journals. Methods and Results Using the Medline database, we retrieved cardiovascular medicine‐related systematic reviews and meta‐analyses published in The New England Journal of Medicine, The Lancet, Journal of the American Medical Association, The British Medical Journal, Annals of Internal Medicine, Circulation, European Heart Journal, and Journal of American College of Cardiology between January 1, 2012 and December 31, 2018. Among 6406 original investigations published during the study period, meta‐analyses represented 422 (6.6%) articles, with an annual decline in the proportion of published meta‐analyses (8.7% in 2012 versus 4.6% in 2018, Ptrend=0.002). A substantial number of studies failed to incorporate elements of Preferred Reporting Items for Systematic Reviews and Meta‐Analyses or Meta‐Analysis of Observational Studies in Epidemiology guidelines (51.9%) and only a minority of studies (10.4%) were registered in PROSPERO (International Prospective Register of Systematic Reviews). Fewer manuscripts failed to incorporate the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses or Meta‐Analysis of Observational Studies in Epidemiology elements over time (60.2% in 2012 versus 40.0% in 2018, Ptrend<0.001) whereas the number of meta‐analyses registered at PROSPERO has increased (2.4% in 2013 versus 17.5% in 2018, Ptrend<0.001). Conclusions The proportion of cardiovascular medicine‐related meta‐analyses published in the highest impact journals has declined over time. Although there is an increasing trend in compliance with quality‐based guidelines, the overall compliance remains low.